Effect of Estrous Cycle on Behavior of Females in Rodent Tests of Anxiety - Lovick, Thelma A.; Zangrossi, Hélio (Frontiers in Psychiatry, 2021)
Anxiety disorders are more prevalent in women than in men. In women the menstrual cycle introduces another variable; indeed, some conditions e.g. premenstrual syndrome, are menstrual cycle specific. Animal models of fear and anxiety, which form the basis for research into drug treatments, have been developed almost exclusively, using males. There remains a paucity of work using females and the available literature presents a confusing picture. One confound is the estrous cycle in females, which some authors consider, but many do not. Importantly, there are no accepted standardised criteria for defining cycle phase, which is important given the rapidly changing hormonal profile during the 4 day cycle of rodents. Moreover, since many behavioural tests that involve a learning component or that consider extinction of a previously acquired association require several days to complete; the outcome may depend on the phase of the cycle on the days of training days as well as on test days. In this article we consider responsiveness of females compared to males in a number of commonly used behavioral tests of anxiety and fear that wwere dceveloped in male rodents. We conclude that females perform in a qualitatively similar manner to males in most tests although there may be sex and strain differences in sensitivity. Tests based on unconditioned threatening stimuli are significantly influenced by estrous cycle phase with animals displaying increased responsiveness in the late diestrus phase of the cycle (similar to the premenstrual phase in women). Tests that utilise conditioned fear paradigms, which involve a learning component appear to be less impacted by the estrous cycle although sex and cycle-related differences in responding can still be detected. Ethologically-relevant tests appear to have more translational value in females. However, even when sex differences in behavior are not detected, the same outward behavioral response may be mediated by different brain mechanisms. In order to progress basic research in the field of female psychiatry and psychopharmacology, there is a pressing need to validate and standardise experimental protocols for using female animal models of anxiety-related states.